Tolerant and Moderate Islamic Religious Practices in Pesantren Al-Qodir - Miftahuddin, Miftahuddin (UIN Maulana Malik Ibrahim Malang, 2023)
Creating peace and harmony among communities is an Islamic teaching must be implemented to achieve goodness and harmony among humanity. It is what K.H. Masrur Ahmad MZ and his pesantren are currently doing, not only in theory but also in practice. This article aims to explain the practice of a tolerant and moderate interpretation of Islam, or often referred to as